Comparative Morphology of Ethmalosa fimbriata (Bowdich, 1825) From Three Estuaries Adjoining the Gulf of Guinea, Nigeria - Eriegha, Ochuko Joshua; Ekelemu, Jerimoth Kesena; Nwachi, Oster Francis (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Environmental interactions have long been considered an important factor in morphological differentiation in fish species. This study evaluated the morphological variations in Ethmalosa fimbriata from three water bodies (Qua Iboe estuary, Escravos estuary, and Lagos lagoon) adjoining the Gulf of Guinea, Nigeria. Fish samples were collected with the assistance of fishers using nets and were taken to the laboratory, where they were identified. Morphological evaluations were thereafter made on a total of 450 samples, comprising 150 random samples from each water body. Fish from the Qua Iboe estuary and Lagos lagoon shared the most morphometric characteristics (weight, standard length, dorsal fin base, and caudal peduncle length) that were significantly different (P< 0.05) from those in the Escravos estuary. The length-weight regression of E. fimbriata can be described by the following equation: W = 0.163TL2.7078, W = 0.1915TL1.4322, and W = 0.2039TL1.4394 for Qua Iboe estuary, Escravos estuary, and Lagos lagoon, respectively. The regression coefficient b revealed that all three populations of E. fimbriata had a negative allometric growth pattern. Fish samples from the Lagos lagoon had the highest condition factor (1.01±0.02) while those from the Escravos estuary had the least (0.79±0.02). Conclusively, the study revealed that E. fimbriata from the Escravos estuary was less fit compared with the other water bodies. This may be attributed to crude oil pollution, overfishing, and frequent water disturbance by vessels. The data generated is critical to understanding population dynamics and further contributing to sustainable fisheries practices, management, and conservation efforts.